2019
DOI: 10.1021/acsami.9b17160
|View full text |Cite
|
Sign up to set email alerts
|

Robust Ag/ZrO2/WS2/Pt Memristor for Neuromorphic Computing

Abstract: The development of the information age has made resistive random access memory (RRAM) a critical nanoscale memristor device (MD). However, due to the randomness of the area formed by the conductive filaments (CFs), the RRAM MD still suffers from a problem of insufficient reliability. In this study, the memristor of Ag/ ZrO 2 /WS 2 /Pt structure is proposed for the first time, and a layer of two-dimensional (2D) WS 2 nanosheets was inserted into the MD to form 2D material and oxide double-layer MD (2DOMD) to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 61 publications
2
114
1
1
Order By: Relevance
“…The Hebbian learning rule, an essential neural theory, reflects the effect of pre‐synaptic and post‐synaptic activity 40,41. One of the most important biological features underlying this theory is the spike‐time‐dependent plasticity (STDP) 42,43. Adjusting the weights of synapses according to the time (Δ t ) is an important feature of STDP.…”
Section: Resultsmentioning
confidence: 99%
“…The Hebbian learning rule, an essential neural theory, reflects the effect of pre‐synaptic and post‐synaptic activity 40,41. One of the most important biological features underlying this theory is the spike‐time‐dependent plasticity (STDP) 42,43. Adjusting the weights of synapses according to the time (Δ t ) is an important feature of STDP.…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical reaction is responsible for the switching behavior in this type of synapse, [36,54] which generally utilizes electrochemically active (e.g., Ag and Cu) and inert (e.g., Pt and Au) metals as the two-terminal electrodes. [39,[64][65][66][67][68][69][70][89][90][91][92][93][94] Furthermore, diverse solid electrolyte materials, such as Ag 2 S, [39,67] Cu 2 S, [89] α-Si, [90] SiO 2 , [92] and Ta 2 O 5 , [93,94] have been used as the active layer. For example, when a negative bias is applied to the inert electrode, the active Ag (or Cu) electrode at the interface becomes oxidized by the charge transfer reaction, and thus resulting in the formation of Ag + cations.…”
Section: Electrochemical Metallization Synapsementioning
confidence: 99%
“…Hence, a wide range of electrochemical metallization memristive synapses has recently been suggested and developed. [39,[64][65][66][67][68][69][70][89][90][91][92][93][94] For example, Shi et al reported amorphous ZrTe alloy/Al 2 O 3 /Ta memristive synapses. [64] In this structure, the Te-based conductive filament grew by the migration and nucleation of Te + cations at the interface that can be controlled by the applied electric field.…”
Section: Electrochemical Metallization Synapsementioning
confidence: 99%
“…Finally, heterojunction-structure devices, where the active switching layer consists of 2D-2D or 2D-3D hybrid heterojunctions instead of a single material, operate based on the filament formation, charge trapping, and vacancy migration mechanisms unlike the previously suggested structures. [62][63][64] While phase transition, [65][66][67] vacancy migration, [68][69][70] filament formation, [71][72][73] and charge trapping [74][75][76] are reported commonly in both bulk and 2D materials, migration of specific defects, phase transition induced by cation migration, and SE to DT transition in a atomically thin active layer are uniquely observed in the 2D platform. Table 1 categorizes the mechanisms of the memristive switching according to the structures and materials and further summarizes synaptic functions with characteristic features such as SET voltage (V SET ), operation current, power consumption, and stability.…”
Section: Introductionmentioning
confidence: 99%
“…d) STDP characteristics with 0.8 V pulse amplitude and 100 ns pulse width. a-d) Reproduced with permission [62]. Copyright 2019, American Chemical Society.poly(ethylene naphthalate) foil substrates with inkjet-printed bottom Ag electrodes, were oxidized in air at 200 °C to form an ultrathin (<3 nm) oxide layer as a switching layer.…”
mentioning
confidence: 99%